Recent advances in immunotherapy targeting CETP proteins for atherosclerosis prevention - Wenhui Hu; Han Feng; Ying Liu; Xiaoshuang Xu; Ping Zhou; Zhonghua Sun; Xinyu Tao; Jiahui Yang; Jun Wu; Chen Qu; Zhengxia Liu (Human Vaccines & Immunotherapeutics)
Cholesteryl ester transfer protein (CETP) plays a key role in lipoprotein metabolism, and its activity has been linked to the risk of atherosclerosis (AS). CETP inhibitors, such as obicetrapib, represent a novel approach in immunotherapy to reduce the risk of atherosclerotic cardiovascular disease (ASCVD) by targeting lipid metabolism. In addition, CETP vaccines are being explored as a novel strategy for the prevention and treatment of ASCVD by inducing the body to produce antibodies against CETP, which is expected to reduce CETP activity, thereby increasing high-density lipoproteins (HDL) levels. This paper provides a comprehensive overview of the structure of CETP, the mechanisms of lipid transfer and the progress of immunotherapy in the last decade, which provides possible ideas for future development of novel drugs and optimization of immunization strategies.